ICU Use and Quality of Care for Patients With Myocardial Infarction and Heart Failure - Valley, Thomas S. (Chest, 2016)
BACKGROUND: Quality of care for acute myocardial infarction (AMI) and heart failure (HF) varies across hospitals, but the factors driving variation are incompletely understood. We evaluated the relationship between a hospital’s ICU or coronary care unit (CCU) admission rate and quality of care provided to patients with AMI or HF. METHODS: A retrospective cohort study of Medicare beneficiaries hospitalized in 2010 with AMI or HF was performed. Hospitals were grouped into quintiles according to their risk- and reliability-adjusted ICU admission rates for AMI or HF. We examined the rates that hospitals failed to deliver standard AMI or HF processes of care (process measure failure rates), 30-day mortality, 30-day readmissions, and Medicare spending after adjusting for patient and hospital characteristics. RESULTS: Hospitals in the lowest quintile had ICU admission rates < 29% for AMI or < 8% for HF. Hospitals in the top quintile had rates > 61% for AMI or > 24% for HF. Hospitals in the highest quintile had higher process measure failure rates for some but not all process measures. Hospitals in the top quintile had greater 30-day mortality (14.8% vs 14.0% [P = .002] for AMI; 11.4% vs 10.6% [P < .001] for HF), but no differences in 30-day readmissions or Medicare spending were seen compared with hospitals in the lowest quintile. CONCLUSIONS: Hospitals with the highest rates of ICU admission for patients with AMI or HF delivered lower quality of care and had higher 30-day mortality for these conditions. Hospitals with high ICU use may be targets to improve care delivery.